2010
DOI: 10.1586/ern.09.135
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and headache: a bidirectional relationship

Abstract: Sleep and pain perception are two phylogenetically well-conserved functions, strictly influenced by environmental and psychological factors, and are able to interact reciprocally both in physiological and pathological situations. Sleep and head-pain perception share the involvement of several structures, such as the thalamus, the hypothalamus and brainstem nuclei, including the locus coeruleus and raphe nuclei. There ais clinical evidence indicating that sleep disorders can precede the appearance of certain he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 120 publications
(138 reference statements)
1
29
0
2
Order By: Relevance
“…Since then, several aspects of the comorbidity between sleep and headache have been investigated and confirmed by the medical literature 35…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since then, several aspects of the comorbidity between sleep and headache have been investigated and confirmed by the medical literature 35…”
Section: Introductionmentioning
confidence: 94%
“…Children who suffer from headache have usually a high rate of sleep difficulties, including insufficient sleep, cosleeping, difficulties falling asleep, anxiety related to sleep, restless sleep, night waking, nightmares, and fatigue during the day 5,7. Different surveys in large pediatric populations have confirmed the strong association between headache and different sleep disorders, such as parasomnias, insomnia, sleep-breathing disorders, and daytime sleepiness 1820…”
Section: Incidence and Prevalence Of Sleep Disorders In Headache And mentioning
confidence: 99%
“…Other workers found that heavy snorers are more likely to suffer from morning headaches 58 . The relationship of morning headache with nocturnal respiratory patterns and architectural sleep parameters is poorly established 8,59 . Nocturnal hypoxemia has been hypothesized to be the cause of headache early after waking up, but data are contradictory 65,68 .…”
Section: Obstructive Sleep Apnea (Osas)mentioning
confidence: 99%
“…Clinical implications are considered and the management of sleep disorder‐associated headaches is addressed. Comprehensive reviews on this matter that have been published previously may offer additional valuable information to the reader 4‐8 …”
mentioning
confidence: 99%
“…Sleep and pain perception are two phylogenetically wellconserved functions, strictly influenced by environmental and psychological factors, and are able to interact reciprocally both in physiological and pathological situations 32 . In a study on sleep among tension-type headache patients, it was observed that these patients presented with more anxiety, insomnia and fatigue during the day and lower subjective quality of sleep than did healthy controls, despite presenting with a normal duration of sleep in diaries and in polysomnographic examinations.…”
mentioning
confidence: 99%